In situ sulfur loading in graphene-like nano-cell by template-free method for Li–S batteries. Issue 8 (8th February 2018) - Du, Huiwei; Gui, Xuchun; Yang, Rongliang; Lin, Zhiqiang; Liang, Binghao; Chen, Wenjun; Zheng, Yongjia; Zhu, Hai; Chen, Jun
Abstract : Hollow graphene-like nano-cells were prepared as the host with high in situ sulfur loading via a template-free method for high-performance lithium–sulfur batteries. Abstract : Carbon nanomaterials with 3D structures as sulfur hosts have been widely developed in lithium–sulfur batteries because of their high specific surface area, high conductivity and structural stability. However, sulfur, loaded by melting-diffusion method, is usually attached to the outside surface of carbon host, resulting in weak adsorption to expose polysulfide. Herein, we report a template-free method for synthesizing graphene-like nano-cell (GLC) with high in situ sulfur loading (S@GLC). The GLC is expected to provide physical adsorption by enclosed graphene cell architecture and chemical adsorption by pyridinic N-doping and oxygen functional group. With these merits, the S@GLC cathode owned high sulfur content (72%) and also, it exhibited a reversible specific capacity of 1253 mA h g −1 at 0.2C, excellent rate performance, and long cycling stability (502 mA h g −1 after 400 cycles at 1C).